Workplace Environment's Impact on Employee Engagement: Social Cognitive Perspective - Meyvanali; Manalu, Della Edelweiss; Sibatuara, Rahel Gabriel Rosabeth (Universitas Pelita Harapan, 2024)
This study aims to investigate the impact of the work environment on employee engagement, which in turn influences performance from a social-cognitive perspective. Several studies have demonstrated that positive environments can enhance employees' engagement with the organization and ultimately lead to improved performance. The social-cognitive perspective asserts that interaction between personal factors, environment, and behavior shapes individual behavior patterns. The method used is systematic literature review, which involves analyzing pertinent empirical research studies and comprehensively reviewing previous relevant international literature revieThe study examines workplace environments and factors that influence work engagement, which are linked to performance, using social theory to understand their significance. ng. This study shows that a positive workplace environment through social-cognitive theory has been shown to increase self-efficacy, engagement, and ultimately performance. Therefore, organizations need to pay attention to aspects of the workplace environment